2022
DOI: 10.1002/cbin.11799
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates hypoxia‐induced cardiomyocyte injury by promoting telomere/telomerase activity: Possible involvement of ERK1/2‐Nrf2 signaling pathway

Abstract: Dexmedetomidine (Dex), an α2‐adrenergic receptor (α2‐AR) agonist, possesses cardioprotection against ischemic/hypoxic injury, but the exact mechanism is not fully elucidated. Since telomere/telomerase dysfunction is involved in myocardial ischemic damage, the present study aimed to investigate whether Dex ameliorates cobalt chloride (CoCl2; a hypoxia mimic agent in vitro)‐induced the damage of H9c2 cardiomyocytes by improving telomere/telomerase dysfunction and further explored the underlying mechanism focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The mechanisms of right ventricular remodeling and failure are complex, pathological features with cardiomyocyte hypertrophy and myocardial injury, and those mechanisms remain unclear. It`s reported that inflammation is pathogenic in PH, and Nrf2 or ERK1/2-Nrf2 signaling pathway may be a target to prevent or reverse PH [23,24]. CD38 inhibits SIRT3 expression and activates of Ca 2+ -NFAT, playing an essential role in cardiac hypertrophy [25].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of right ventricular remodeling and failure are complex, pathological features with cardiomyocyte hypertrophy and myocardial injury, and those mechanisms remain unclear. It`s reported that inflammation is pathogenic in PH, and Nrf2 or ERK1/2-Nrf2 signaling pathway may be a target to prevent or reverse PH [23,24]. CD38 inhibits SIRT3 expression and activates of Ca 2+ -NFAT, playing an essential role in cardiac hypertrophy [25].…”
Section: Discussionmentioning
confidence: 99%
“…PKC phosphorylated Nrf2 and activated its detachment from Keap1. ERK1/2 has also been reported to have mediated the antioxidative effect of DEX by participating in Nrf2 activation and translocation into the nucleus ( 56 ). In addition to the two aforementioned kinases, the MAPK signaling pathway ( 57 ) and certain microRNAs (miRNAs), such as miRNA (miR)-27a, miR-153, miR142-5p and miR-144 ( 58 ), have also been reported to have mediated the regulation of Nrf2 expression and its activation.…”
Section: Discussionmentioning
confidence: 99%
“…5 attenuates IR-induced ICM through inhibiting ferroptosis by decreasing the production of LPO, increasing the Nrf2 and GPX4 protein, while decreasing the mRNA levels of Ptgs2 and Acsl4 , and the protein levels of ACSL4 ( Lin et al, 2021 ). Dexmedetomidine (6) , a highly selective alpha2-adrenoceptor agonist with sedative, analgesic, sympatholytic, and hemodynamic-stabilizing properties, posess the protective effect against I/R ( Xiao Z. et al, 2021 ; Chen Y. et al, 2021 ; Deng et al, 2022 ; Yang et al, 2022 ; Hu et al, 2023 ) and H/R ( Wu W. et al, 2022 ; Wang L. et al, 2022 ) induced cardiomyocyte injury. 6 attenuates ICM through inhibiting ferroptosis by activating AMPK/GSK-3β-dependant Nrf2/SLC7A11/GPX4 ( Wang et al, 2022d ).…”
Section: Pharmacological Inhibition Of Ferroptosis For Treating Cardi...mentioning
confidence: 99%